The equivalence between the Hamiltonian and Lagrangian formulations for the parametrization-invariant theories - S. I. Muslih (International Journal of Mathematics and Mathematical Sciences)
The link between the treatment of singular Lagrangians as field systems and the canonical Hamiltonian approach is studied. It is shown that the singular Lagrangians as field systems are always in exact agreement with the canonical approach for the parametrization invariant theories.